Protease‐activated receptor 2 does not contribute to renal inflammation or fibrosis in the obstructed kidney. Issue 9 (31st July 2019) - Ma, Frank Y; Han, Yingjie; Ozols, Elyce; Chew, Phyllis; Vesey, David A; Gobe, Glenda C; Morais, Christudas; Lohman, Rink‐Jan; Suen, Jacky Y; Johnson, David W; Fairlie, David P; Nikolic‐Paterson, David J
ABSTRACT: Aim: Protease‐activated receptor 2 (PAR2) has been implicated in the development of renal inflammation and fibrosis. In particular, activation of PAR2 in cultured tubular epithelial cells induces extracellular signal‐regulated kinase signalling and secretion of fibronectin, C–C Motif Chemokine Ligand 2 (CCL2) and transforming growth factor‐β1 (TGF‐β1), suggesting a role in tubulointerstitial inflammation and fibrosis. We tested this hypothesis in unilateral ureteric obstruction (UUO) in which ongoing tubular epithelial cell damage drives tubulointerstitial inflammation and fibrosis. Methods: Unilateral ureteric obstruction surgery was performed in groups ( n = 9/10) of Par2−/− and wild type (WT) littermate mice which were killed 7 days later. Non‐experimental mice were controls. Results: Wild type mice exhibited a 5‐fold increase in Par2 messenger RNA (mRNA) levels in the UUO kidney. In situ hybridization localized Par2 mRNA expression to tubular epithelial cells in normal kidney, with a marked increase in Par2 mRNA expression by tubular cells, including damaged tubular cells, in WT UUO kidney. Tubular damage (tubular dilation, increased KIM‐1 and decreased α‐Klotho expression) and tubular signalling (extracellular signal‐regulated kinase phosphorylation) seen in WT UUO were not altered in Par2−/− UUO. In addition, macrophage infiltration, up‐regulation of M1 (NOS2) and M2 (CD206) macrophage markers, and up‐regulation of pro‐inflammatory molecules (tumour necrosis factor, CCL2, interleukin‐36α) in WT UUO kidney were unchanged in Par2−/− UUO. Finally, the accumulation of α‐SMA+ myofibroblasts, deposition of collagen IV and expression of pro‐fibrotic factors (CTGF, TGF‐β1) were not different between WT and Par2−/− UUO mice. Conclusion: Protease‐activated receptor 2 expression is substantially up‐regulated in tubular epithelial cells in the obstructed kidney, but this does not contribute to the development of tubular damage, renal inflammation or fibrosis. SUMMARY AT A GLANCE: This study reported that protease‐activated receptor 2 (PAR2) did not contribute to the renal tubular inflammation and fibrosis in a 7‐day model of unilateral ureteric obstruction using PAR2 knockout mice.